Proceedings of Pedestrian and Evacuation Dynamics 2016 - Song, Weiguo; Ma, Jian; Fu, Libi (Collective Dynamics, 2017)
The 8th International Conference on Pedestrian and Evacuation Dynamics (PED 2016) has been held on October 17–21, 2016 in Hefei, China. PED 2016 Conference offered an opportunity for professionals and scientists with different backgrounds to present and discuss new findings and applications in the field of pedestrian and evacuation dynamics and associated human behavior. The conference aims to provide suggestions for policy makers, planners, designers and emergency management to solve real world problems. Conference topics included, but was not limited to: Pedestrian movement mechanisms Pedestrian behavior during disasters: theories, analysis, conclusions Evacuation and pedestrian data collection from experiments and real events Data collection techniques Model development Large-scale and transport modeling methods Model validation/calibration Public transport transfer terminals Regional evacuation Operational management of highly populated facilities Engineering guidance Citation: Please cite the full conference proceedings as follows: Song, W., Ma, J., Fu, L.; Proceedings of Pedestrian and Evacuation Dynamics 2016, Collective Dynamics, A11, 1-618 (2016). DOI 10.17815/CD.2016.11 Single articles inside the proceedings should be cited as: Authors; Title. In: Proceedings of Pedestrian and Evacuation Dynamics 2016, Collective Dynamics, pages (2016) Example: Dambalmath, P., Muhamad, B., Haug, E., Löhner, R.; Fundamental Diagrams for Specific Very High Density Crowds. In: Proceedings of Pedestrian and Evacuation Dynamics 2016, Collective Dynamics, 6-11 (2016)